Characterization of biologic response modifiers in the supernatant of conventional, refrigerated, and cryopreserved platelets. Issue 4 (12th January 2018) - Johnson, Lacey; Tan, Shereen; Jenkins, Emily; Wood, Ben; Marks, Denese C.
Abstract : BACKGROUND: Alternatives to room temperature storage of platelets (PLTs) are of interest to support blood banking logistics. The aim of this study was to compare the presence of biologic response modifiers (BRMs) in PLT concentrates stored under conventional room temperature conditions with refrigerated or cryopreserved PLTs. STUDY DESIGN AND METHODS: A three‐arm pool‐and‐split study was carried out using buffy coat–derived PLTs stored in 30% plasma/70% SSP+. The three matched treatment arms were as follows: room temperature (20‐24°C), cold (2‐6°C), and cryopreserved (–80°C with DMSO). Liquid‐stored PLTs were tested over a 21‐day period, while cryopreserved PLTs were tested immediately after thawing and reconstitution in 30% plasma/70% SSP+ and after storage at room temperature. RESULTS: Coagulation factor activity was comparable between room temperature and cold PLTs, with the exception of protein S, while cryopreserved PLTs had reduced Factor (F)V and FVIII activity. Cold‐stored PLTs retained α‐granule proteins better than room temperature or cryopreserved PLTs. Cryopreservation resulted in 10‐fold higher microparticle generation than cold‐stored PLTs, but both groups contained significantly more microparticles than those stored at room temperature. The supernatant from both cold and cryopreserved PLTs initiated faster clot formation and thrombin generation than room temperature PLTs. CONCLUSION: Cold storage and cryopreservation alter the composition of the soluble fraction of stored PLTs. These differences in coagulation proteins, cytokines, and microparticles likely influence both the hemostatic capacity of the components and the auxiliary functions.